Ascoschoengastia octavia Domrow 1962 - Stekolnikov, Alexandr A. (Zenodo, 2021)
Ascoschoengastia octavia Domrow, 1962 Ascoschoengastia (Laurentella) octavia Domrow, 1962a: 588, figs. 10–18. Ascoschoengastia (Ascoschoengastia) octavia : Vercammen-Grandjean 1965b: 91; 1968b: 93. Ascoschoengastia (Laurentella) octovia (sic): Chau et al. 2007: 116. Type deposition. BMNH 1962.8.10.24. Type data. Ex Tupaia glis , Vietnam, Phan Rang, Nya Ho Agricultural Station. Hosts. RODENTIA: Menetes berdmorei moerescens, Niviventer niviventer, Rattus rattus SCANDENTIA: Tupaia glis . Distribution. Vietnam. Published as part of Stekolnikov, Alexandr A., 2021, A checklist of chigger mites (Acariformes: Trombiculidae) of Southeast Asia, pp. 1-163 in Zootaxa 4913 (1) on page 76, DOI:10.11646/zootaxa.4913.1.1, http://zenodo.org/record/4448915